Impact behaviors of epoxy/glass fiber composites at subzero and elevated temperatures - Mridha, Shahjahan (IIUM Press, 2009)
Fiber reinforced epoxy composite specimens of different volume fractions of woven or chopped fibers were fabricated using manual lay up process. To obtain higher fiber volume fraction, a greater force is needed to consolidate the chopped fiber composite than for the woven fiber one. The impact testing for fracturing the specimen was conducted at temperatures between -50 and +50°C. The impact energy absorption for fracturing the specimens containing different fiber volume fractions was found to be higher at +50°C and the value decreased when tested at lower temperatures. The reduction of energy absorption was not significant below subzero temperatures. At +50°C, the 52 vol% woven fiber composite gave the highest specific energy absorption of 400KJm while it was only around 270KJm with chopped fiber specimens and 220KJm for chopped fiber ones. The woven fiber composite failed with high deformation, buckling, delamination and large matrix cracking at +50°C while at -50°C, the samples failed with less deformation, matrix cracking, fiber splitting and micro delimination. At +50°C, the chopped samples gave high deformation, fiber imprint mark and fiber protrusion while at -50°C, failed with less deformation, but serve bundle splitting.